Urogenital pathology, herpetic infection and the state of immunity - M. V. Novikov; V. S. Goydyk (Kazimierz Wielki University, 2019)
The main indexes of immune status have been learnt in 150 patients with urogenital infection. The results obtained were compared with those of 30 healthy volonteers.  The disturbanses of immunity and formation of the secondary immunodeficiency in the group of patients with virus damage of urogenital system had been revealed. To correct timely therapeutic schemes and increase the treatment's efficacy additional researches are necessary.